Rejecting Standard Care. Issue 5 (September 2015) - Bauer, Jill A.
<x xml:space="preserve">Abstract</x> Parental refusal of vitamin K administration for newborns after birth is on the rise. How can nurses provide adequate information to assist parents in making a truly informed choice about vitamin K so risk of unnecessary harm to babies can be minimized?